Engineering xylose utilization in Yarrowia lipolytica by understanding its cryptic xylose pathway. Issue 1 (December 2016) - Rodriguez, Gabriel; Hussain, Murtaza; Gambill, Lauren; Gao, Difeng; Yaguchi, Allison; Blenner, Mark
Abstract Background The oleaginous yeast, Yarrowia lipolytica, has been utilized as an industrial host for about 60 years for various applications. Recently, the metabolic engineering of this host has become increasingly popular due to its ability to accumulate lipids as well as improvements made toward developing new genetic tools.Y. lipolytica can robustly metabolize glucose, glycerol, and even different lipid classes. However, little is known about its xylose metabolizing capability. Given the desirability of having a robust xylose utilizing strain ofY. lipolytica, we performed a comprehensive investigation and elucidation of the existing components of its xylose metabolic pathway. Results A quick and efficient means of determining functionality of the candidate xylose pathway genes (XYR, XDH, and XKS) fromY. lipolytica was desirable. We challengedEscherichia coli mutants lacking either the xylose isomerase (xylA ) gene or the xylulose kinase (xylB ) gene to grow on xylose minimal media by expressing the candidate genes fromY. lipolytica . We showed that the XKS ofY. lipolytica is able to rescue xylose growth ofE. coli ΔxylB, and the XDH enabled growth on xylitol, but not on xylose, ofE. coli ΔxylA . Overexpression of XKS and XDH inY. lipolytica improved growth on xylitol, indicating that expression of the native enzymes was limiting. Overexpression of XKS and XDH inY. lipolytica also enables robust growth on xylose under high nitrogen conditions without the need for adaptation. These results prove that a complete xylose pathway exists inY. lipolytica, but the pathway is poorly expressed. To elucidate the XYR gene, we applied theE. coli ΔxylA xylose growth challenge with 14 candidate XYR genes and XDH. The XYR2 candidate was able to rescue growth ofE. coli ΔxylA xylose on minimal media. Conclusions While a native xylose pathway exists inY. lipolytica, the microorganism's inability to grow robustly on xylose is an effect of cryptic genetic circuits that control expression of key enzymes in the metabolic pathway. We have characterized the key enzymes associated with xylose metabolism and demonstrated that gene regulatory issues can be overcome using strong hybrid promoters to attain robust growth on xylose without adaptation.